Successful surgical closure and continence rate of obstetric fistula in Africa: systematic review and meta-analysis - Kumsa, Henok; Mislu, Esuyawkal; Arage, Mulugeta Wedaje; Abera, Atitegeb; Hailu, Tilahun; Tenaw, Lebeza Alemu (Frontiers in Global Women's Health, 2023)
Background: A female genital fistula is an abnormal connection between a woman's reproductive tract and her urinary tract, or rectum. While numerous studies have aimed to determine the success rate of obstetric fistula closure in different health settings, there remains a significant scarcity of data on closure success rates and incontinence rates for various types of fistula at the regional and sub-regional levels. The success rate reflects the continent's healthcare setup in regard to World Health Organization standard. Thus, this study aims to determine the success of surgical closure and continent rate of obstetric fistula in Africa.Methods: This systematic review and meta-analysis review included studies conducted up to February 2023. Search engines like EMBBASE, Medline, Google, PubMed, Google scholar, African journal online and science direct databases were utilized to find articles. The Joanna Briggs Institute critical evaluation checklist was used to evaluate the quality of our review, which was conducted precisely in accordance with PRISMA criteria. Heterogeneity was indicated by the p-value for I 2 statistics less than 0.05. The publication bias was assessed using the Egger regression asymmetry test. Data were entered into Microsoft Excel, and analyze using STATA 16.Result: This review included 85 studies. A total of 24 countries from East, West, Central, North and Southern African sub-regions were included. The overall pooled estimate rate of obstetrics fistula successful closure is . Moreover, the pooled estimate of vesico-vaginal fistula successfully closed but with ongoing or residual incontinence (wet) revealed 13.41% . The pooled estimate of rectovaginal fistula and combined VVF and RVF successfully closure rate is 91.06% (95%CI: 86.08-96.03) and 62.21% (95% CI: 48.94-75.49) respectively.The rate of successful obstetric fistula closure in Africa is 86.15, which is higher than the WHO target. However, the surgical closure rate of a combined VVF and RVF is 62.2%, which is significantly lower than the WHO target.